Studying the Personality Disorders and clinical signs in aggression attempter in the Public Places of sanandaj City - Farideh Faraji (روانشناسی و روانپزشکی شناخت, 2015)
Objective: The aim of the current research was to determine of the Personality Disorders and clinical signs in aggression attempter in the Public Places of sanandaj City. Method: This research was a descriptive study, targeting all Aggression attempter referred to the commissariat due to aggression attempt in Public Places of sanandaj City that were selected 102 attempter (87 males and 15 females) by convenience sampling. Data were collected by Demographic questionnaire and Millon Multi-axial personality inventory-III (MCMI-III). The data were analyzed by SPSS and used the MANOVA. Results: results showed that the highest personality disorders respectively include of Hystrionic, narcissist, depression and lowest include of dependence, schizotypal, avoidance, passive- aggression. the highest clinical disorders respectively include of dysthymia, Thought disorder, major depression, and the lowest include of Delusion Disorder and PTSD. There was significant difference between two groups in the all personality disorders except passive aggression, obsessive-compulsion and in the all clinical disorders except PTSD and somatoform (p≤./.5). Conclusion: The findings of this study can be helpful in identifying and preventing aggression in the Public Places as Social problem.